The Knights Templar on trial: the trial of the Templars in the British Isles, 1308 - 1311 - Nicholson, Helen J. (History Press, 2009)
The beginning of the trial of the Templars -- The arrests in the British Isles -- The Templars' lands in royal hands -- The interrogations in England -- The trial in Scotland : mixed reactions -- The trial in Ireland : 'all the Templars are guilty' -- The end of the trial in the British Isles -- Conclusion : The Council of Vienne and the end of the Templars